2017
DOI: 10.3390/bdcc1010004
|View full text |Cite
|
Sign up to set email alerts
|

Smart Cities, Big Data, and Sustainability Union

Abstract: Media convergence has changed relationships between existing technologies, industries, markets, and audiences. Smart cities are seen as the logical outcome of media convergence. Big Data form the basis and the output of smart technologies. In the last twenty years, there has been much discussion on smart cities, big data, and the need for sustainability in technological endeavors. This article combines these by providing an overview of the three subjects about their points of intersection. Identifying these po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…The authors have proposed the model of big smart city data management and evaluated the technological architecture and challenges. A few generic reviews or the discussion of big data in smart cities can be found in [72][73][74][75], while the role of sustainability in smart cities is exploited in [76,77].…”
Section: Sustainable Urban Planning and Infrastructurementioning
confidence: 99%
“…The authors have proposed the model of big smart city data management and evaluated the technological architecture and challenges. A few generic reviews or the discussion of big data in smart cities can be found in [72][73][74][75], while the role of sustainability in smart cities is exploited in [76,77].…”
Section: Sustainable Urban Planning and Infrastructurementioning
confidence: 99%
“…For example, the strategic assessment and evaluation of the effects of information and communications technology (ICT) require competent governance models, as well as the adoption of well-balanced top-down and bottom-down approaches. These obstacles are also discussed by Kudva and Ye [38] where several obstacles including socioeconomic inequalities and the digital divide hinder cities becoming smart and sustainable. The findings of these also tend to agree with several other studies [39][40][41] showing the country or region-specific obstacles for implementing various smart technologies, strategies, and initiatives to make their cities more sustainable.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Others are, for example, Ward et al [15] and Gandomi et al [16] which assess existing (industry) definitions to find and describe common aspects between them. There is also research focused on definitions within a specific research area, such as: Kudva et al [17] for smart cities, Wolfert et al [18] for smart farming, and Hashem et al [19] for cloud computing. These studies are aimed at helping researchers identifying the intersections between the research area that they know and BD.…”
Section: Related Workmentioning
confidence: 99%